x = 2
_________ ___________ __________ __________ __________
–3(x + 1) = 2(x – 8) + 3
-3x - 3 = 2x - 16 + 3
-5x = -10
x = -10/-5
x = 2
_________ __________ __________ ___________ __________
Verification:
- 3(x + 1) = 2(x - 8) + 3
- 3(2 + 1) = 2(2 - 8) + 3
- 3(3) = 2(- 6) + 3
- 9 = - 12 + 3
- 9 = - 9
________ x _________ x_________ x _________ x _________
2007-01-21 03:19:20
·
answer #1
·
answered by Som™ 6
·
1⤊
0⤋
- 3(x + 1) = 2(x - 8) + 3
- 3x + (- 3) = 2x - 16 + 3
- 3x - 3 = 2x - 13
- 3x - 3 + 3x = 2x - 13 + 3x
- 3 = 5x - 13
- 3 + 13 = 5x - 13 + 13
10 = 5x
10 / 5 = 5x / 5
10 / 5 = x
2 = x
The answer is x = 2
Insert the x value into the equation
- - - - - - - - - - - - - - - - - - - - - - -
Check
- 3( x + 1) = 2(x - 8) + 3
- 3(2 + 1) = 2(2 - 8) + 3
- 3(3) = 2(- 6) + 3
- 9 = - 12 + 3
- 9 = - 9
- - - - - - - - - -s-
2007-01-21 03:26:46
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
x = 2
–3(x + 1) = 2(x – 8) + 3 (you multiply)
-3x - 3 = 2x - 16 + 3
-5x = -10(Divide x on both sides)
x =2
2007-01-21 03:23:46
·
answer #3
·
answered by ??????? 1
·
0⤊
0⤋
-3(x+1) = 2(x-8) + 3
=> -3x-3 = 2x-16 +3
=> 16-3-3 = 2x + 3x
=> 10 = 5x
So, x = 10/5 = 2
x = 2 Answer.
2007-01-21 03:23:04
·
answer #4
·
answered by mani 2
·
0⤊
0⤋
All you have to do is open the brackets, so you have:
-3x - 3 = 2x - 16 + 3
Now isolate the variables:
-5x = -10
x = 2
2007-01-21 03:20:45
·
answer #5
·
answered by San Jose 3
·
0⤊
0⤋
x=2
sucstitute it in place of x &
lhs = rhs.
-------------------------------------
Open the brackets and bring the like terms together,,,
----------------------------------------------------
2007-01-21 03:20:08
·
answer #6
·
answered by ommidikra 2
·
0⤊
0⤋